2020
DOI: 10.1017/wsc.2020.28
|View full text |Cite
|
Sign up to set email alerts
|

Germination ecology of hairy fleabane (Conyza bonariensis) and its implications for weed management

Abstract: Hairy fleabane [Conyza bonariensis (L.) Cronquist] is a problematic weed in Australian no-till cropping systems. Consequently, a study was conducted to examine the effect of temperature, light, salt stress, osmotic stress, burial depth, and sorghum crop residue on germination and emergence in two populations (C and W: collected from chick pea [Cicer arietinum L.] and wheat [Triticum aestivum L.] fields, respectively) of C. bonariensis. Both populations were able to germinate over a wide range of alternating da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 26 publications
3
22
1
Order By: Relevance
“…Several enzymes necessary for seed germination are regulated by temperature; thus, it is an important environmental cue influencing seed germination of weeds and crop plants [ 31 ]. Conyza species successfully germanite under a temperature range of 20 and 30°C, and 20°C is regarded optimum for their seed germination [ 23 , 26 28 , 32 , 33 ]. Nonetheless, some studies have reported that several Conyza species are capable of germinating at higher temperatures [ 24 , 26 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several enzymes necessary for seed germination are regulated by temperature; thus, it is an important environmental cue influencing seed germination of weeds and crop plants [ 31 ]. Conyza species successfully germanite under a temperature range of 20 and 30°C, and 20°C is regarded optimum for their seed germination [ 23 , 26 28 , 32 , 33 ]. Nonetheless, some studies have reported that several Conyza species are capable of germinating at higher temperatures [ 24 , 26 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Conyza species successfully germanite under a temperature range of 20 and 30°C, and 20°C is regarded optimum for their seed germination [ 23 , 26 28 , 32 , 33 ]. Nonetheless, some studies have reported that several Conyza species are capable of germinating at higher temperatures [ 24 , 26 , 32 ]. Due to the reason, inferring seed germination of each species under various environmental cues is necessary for their successful management.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This type of the ‘weed shift’ behavior has previously been observed in many weed species such as Sonchus oleraceus L. [ 26 ], Sisymbrium thellungii O. E. Schulz. [ 27 ] and Conyza bonariensis L. [ 28 ]. However, it should not be implied that successful germination at low temperatures in laboratory conditions means successful survival in field conditions, as frost may kill weed species in winter.…”
Section: Resultsmentioning
confidence: 99%
“…The germination biology of various populations of weed species is known to vary under different environmental conditions (Chadha et al 2019;Loura et al 2020). Within the infestation region in Queensland, Australia, variable environmental conditions occur for rainfall and temperatures, and therefore weed populations may differ in their responses to these different environments and may require different management practices (Cai et al 2005;Iqbal et al 2019;Whitfield and Queensland Department of Environment and Resource Management 2010).…”
Section: Introductionmentioning
confidence: 99%